Poetics and e-literature - Winiecka, Elżbieta (Tematy i Konteksty, 2021)
Following the development of e-literature and the state of research on the subject both in Poland and abroad, the author attempts to outline research perspectives for e-poetics. This discipline, barely over twenty years old, concerns the study of literary texts that are created with the use of digital technologies. Hypertextual works available online and via digital carriers are characterized by intermediality and interactivity, and they differ from printed literature in that computers are indispensable tools for their creation, existence and reception. What are the consequences of this change of medium for literature, its structure, the process of communication with the reader and the interpretative possibilities? How can one describe the relationship between the old and the new form of a literary text? Finally, why is it important to introduce research on electronic literature into academic education?